The relationship between ecological accounting information and financial performance through the moderating role of business sector - Ha, Tran Thi Thu; Du, Tran Thi; Hoa, Nguyen Thi Quynh; Huong, Tran Quynh (Edelweiss Applied Science and Technology, 2025)
The study aims to analyze the relationship between the use of ecological accounting information and financial performance in Vietnamese enterprises and consider the moderating role of the business sector. Data were collected from enterprises operating in various fields such as manufacturing, services, and trade, thereby assessing the level of application of ecological accounting information in the decision-making process and financial management. The results of the study show that the use of ecological accounting information has a positive impact on the financial performance of enterprises by controlling environmental costs, improving operational efficiency, and enhancing compliance with legal requirements related to environmental protection. However, the business sector factor does not show a statistically significant difference in this relationship, meaning that the impact of ecological accounting information on financial performance is similar across types of enterprises. This finding demonstrates the role of ecological accounting in financial management, regardless of the field of operation, and suggests policy and practice recommendations to promote the wider application of ecological accounting in Vietnamese enterprises.